2021
DOI: 10.1136/thoraxjnl-2021-217260
|View full text |Cite
|
Sign up to set email alerts
|

Infections due to dysregulated immunity: an emerging complication of cancer immunotherapy

Abstract: Immune checkpoint inhibitors (ICIs) have revolutionised cancer treatment. However, immune-related adverse events (irAEs) are a common side effect which can mimic infection. Additionally, treatment of irAEs with corticosteroids and other immunosuppressant agents can lead to opportunistic infection, which we have classed as immunotherapy infections due to immunosuppression. However, emerging reports demonstrate that some infections can be precipitated by ICIs in the absence of immunosuppressive treatment, in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 132 publications
2
64
1
Order By: Relevance
“…However, research has found that no significant difference in the use of immunosuppressive agents between patients with and without infections (10,11). Morelli et al suggested that the role of a dysregulated immunity whose mounted response paradoxically favors the pathogen (9). We think that it may be immunotherapy infection due to dysregulated immunity, especially when the patient with psoriasis, which can exacerbate immune disorders.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, research has found that no significant difference in the use of immunosuppressive agents between patients with and without infections (10,11). Morelli et al suggested that the role of a dysregulated immunity whose mounted response paradoxically favors the pathogen (9). We think that it may be immunotherapy infection due to dysregulated immunity, especially when the patient with psoriasis, which can exacerbate immune disorders.…”
Section: Discussionmentioning
confidence: 88%
“…ICIs theoretically do not seem to directly increase the risk of infection ( 6 ) but rather reactivate the cytotoxic T cells that were suppressed by the cancer cells to attack the tumor cells and enhance the immune system ( 7 , 8 ). It was believed that concomitant use of immunosuppressants including systemic corticosteroids with ICIs treatment increased infection risk ( 9 ). However, research has found that no significant difference in the use of immunosuppressive agents between patients with and without infections ( 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that hyperinflammatory dysregulated immunity associated with ICIs drives pathogenesis. These infections are characterized by a dysregulated inflammatory immune response ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence from biological therapeutics and genomic analyses have suggested that we need to refine our concepts of the spectrum of human disease [ 5 , 6 ]. Importantly, this includes confirmation in patients that an excessive immune response can be just as harmful as an insufficient response, as illustrated by increased TB incidence with PD-1 inhibition in cancer immunotherapy [ 6. , 7.…”
Section: Human Tb: the Intricate And Prolonged Contest Between Host And Pathogenmentioning
confidence: 99%